Catalyst coating film, preparation method thereof, membrane electrode and application
By designing a catalyst coated film with multi-stage catalytic layer and metal nanowire structure in PEMWE, the problems of mass transfer resistance of the catalytic layer and interface contact resistance are solved, the catalyst utilization rate and electrolytic performance of the membrane electrode are improved, and the operation is reduced cost.
Patent Information
- Application Number
- CN202310666867.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-06
- Publication Date
- 2024-12-13
AI Technical Summary
The existing PEMWE catalytic layer has a large mass transfer resistance and a large interface contact resistance of the diffusion layer/catalytic layer, resulting in low catalyst utilization and low mass transfer efficiency, which hinders the efficient operation of the membrane electrode.
A catalyst coated film is designed, including an ion exchange membrane and a multi-stage catalytic layer. The multi-stage catalytic layer consists of an ordered arrangement of micro-nano units. The micro-nano units are provided with metal layers and catalytic in sequence along the direction of the ion exchange membrane. The layer and metal nanowires, the catalytic layer are super hydrophilic porous structures, and the metal nanowires are in contact with the metal layer through voids and are formed by hot pressing and alkali washing.
It effectively reduces the plane resistance of the catalytic layer, improves the utilization rate of the catalyst and mass transfer efficiency, optimizes the electrolytic performance of the membrane electrode, and reduces the operating cost of the hydrogen production process.
Smart Images

Figure CN119121275A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst coating membrane and a preparation method thereof, a membrane electrode and application thereof. Background Art
[0002] Proton Exchange Membrane Water Electrolysis (PEMWE) is one of the key technologies to achieve zero-carbon emission hydrogen production. 2 ) has greatly increased the cost of PEMWE and seriously restricted its commercialization process.
[0003] In PEMWE, membrane electrode assemblies (MEA) are one of the core components. High-performance membrane electrodes need to have the characteristics of maximized three-phase reaction interface and efficient mass transfer. At present, in the widely used gas-liquid diffusion layer, fiber structures such as titanium felt and titanium mesh are randomly distributed, resulting in uneven interface contact between them and the catalytic layer. Catalysts that cannot contact the diffusion layer will produce "island" phenomenon and cannot participate in the reaction, resulting in reduced catalyst utilization.
[0004] To solve this problem, researchers have developed ultra-thin titanium plates with adjustable pore size, titanium layers with gradient pore structures, etc. to optimize the interfacial contact between the diffusion layer and the catalytic layer. However, since high porosity is conducive to mass transfer and low porosity can reduce the interfacial contact resistance and the plane resistance of the catalytic layer, high catalyst utilization and efficient mass transfer cannot be achieved at the same time.
[0005] In addition, in order to construct a continuous electron transmission channel at the anode, the researchers designed a nanoneedle macroporous network, a microporous nanosheet catalyst and a self-supporting Ir network structure from the perspective of the catalytic layer structure design. The results showed that these methods can effectively improve the electrical conductivity within the catalytic layer, but the tortuous and narrow pore structure also increases the mass transfer resistance.
[0006] Therefore, it is urgent to develop a catalytic layer structure that has both low catalytic layer planar resistance and fast material transfer channels, which can greatly improve the catalyst utilization rate while achieving efficient mass transfer. Summary of the invention
[0007] The present invention provides a catalyst coated membrane and a preparation method thereof, a membrane electrode and an application thereof to solve the problem that the catalyst coated membrane and membrane electrode in the prior art cannot have both high mass transfer efficiency and high catalyst utilization rate. The catalyst coated membrane of the present invention has super hydrophilicity, and the water electrolysis performance of the membrane electrode prepared therefrom is better than that of the traditional membrane electrode, which solves the problems of large mass transfer resistance of the PEMWE catalyst layer and large contact resistance of the diffusion layer / catalytic layer interface in the prior art, improves catalyst utilization rate and realizes efficient mass transfer.
[0008] The present invention provides a catalyst coating membrane, which comprises an ion exchange membrane and a multi-stage catalyst layer arranged on one side of the ion exchange membrane;
[0009] The multi-stage catalytic layer comprises a plurality of orderly arranged micro-nano units, wherein the micro-nano units are provided with a metal layer, a catalytic layer and metal nanowires in sequence in a direction away from the ion exchange membrane.
[0010] In the present invention, the catalyst coating membrane is structurally designed so that the catalyst layer forms a multi-level micro-nano structure.
[0011] In some embodiments, the micro-nano unit is cylindrical or conical.
[0012] In a preferred embodiment, the thickness of the micro-nano unit is 200 nm-3 μm.
[0013] In a preferred embodiment, the diameter of the maximum cross section of the micro-nano unit is 10 nm-1 μm.
[0014] In a preferred embodiment, the distance between two adjacent micro-nano units is 100 nm-1 μm.
[0015] In a preferred embodiment, the material of the catalytic layer includes IrO2.
[0016] In the present invention, the multi-stage catalytic layer is a super-hydrophilic micro-nano structure.
[0017] In the present invention, the catalyst layer may be a porous structure, and there are gaps on the catalyst layer located above the metal layer, and the metal nanowires may contact the metal layer through the gaps.
[0018] In the present invention, the metal layer enables the metal nanowires to grow in situ at the exposed sites. When the metal layer is not present, the metal nanowires will not grow uniformly, which will reduce the performance of the membrane electrode.
[0019] In some embodiments, the material of the metal layer includes one or more of Au, Pt, Ir, and Pd.
[0020] In some embodiments, the material of the metal nanowires includes one or more of Au, Pt, Ir, and Pd.
[0021] In a preferred embodiment, the material of the metal layer is the same as the material of the metal nanowires.
[0022] In some embodiments, the loading of the metal layer is 0-100 μg / cm 2 , but not 0.
[0023] In some embodiments, the loading of the metal nanowires is 0-0.5 mg / cm 2 , but not 0.
[0024] In some embodiments, the metal nanowires are in one or more of a sea urchin shape, a sphere shape, and a coral shape.
[0025] In some embodiments, the ion exchange membrane comprises a proton exchange membrane or an anion exchange membrane.
[0026] The present invention also provides a method for preparing a catalyst coating membrane, which comprises the following steps:
[0027] S1. Introducing a catalyst slurry and a metal into a template having a micro-nano structure in sequence to form a material A, wherein the material A comprises a metal layer, a catalyst layer and a template arranged in sequence;
[0028] S2, attaching the ion exchange membrane to the metal layer, and then hot pressing to obtain material B, wherein the temperature of the hot pressing is 60-200° C., and the pressure of the hot pressing is 1-60 MPa;
[0029] S3, alkali washing the material B to obtain material C; the alkali washing is used to remove the template;
[0030] S4, immersing the material C in a mixed solution for reaction to form metal nanowires; the mixed solution includes a reducing agent and a metal salt solution.
[0031] In some embodiments, in step S1, the material of the template includes anodized aluminum.
[0032] In some embodiments, in step S1, the template includes a plurality of micro-nano-scale holes.
[0033] In some embodiments, in step S1, the catalyst slurry includes a catalyst, a stereopolymer resin, and a solvent.
[0034] In a preferred embodiment, the catalyst comprises IrO2.
[0035] In the present invention, those skilled in the art should know that the stereopolymer resin plays a role in physically bonding the catalyst to the ion exchange membrane and the gas diffusion layer in the catalyst layer, and also transports protons in the catalyst layer.
[0036] In a preferred embodiment, the stereospecific resin comprises a perfluorosulfonic acid resin.
[0037] In a preferred embodiment, the solvent includes water and alcohol, preferably, the alcohol includes isopropanol.
[0038] In a specific embodiment, the mass ratio of the catalyst, stereopolymer resin, water and alcohol is 1:(1-20):(1-50):(1-50).
[0039] In a preferred embodiment, the method for preparing the catalyst slurry comprises ultrasonically mixing the catalyst, stereopolymer resin and solvent; preferably, the ultrasonic mixing time is 0.1-4h.
[0040] In some embodiments, in step S1, the catalyst slurry is introduced by spraying.
[0041] In some embodiments, in step S1, the metal includes one or more of Au, Pt, Ir and Pd.
[0042] In some embodiments, in step S1, the method of introducing the metal includes ion sputtering and / or magnetron sputtering; preferably, when the method of introducing the metal is ion sputtering, the current of the ion sputtering is 0-50mA, but not 0, and the time of the ion sputtering is 0-360s, but not 0; preferably, when the method of introducing the metal is magnetron sputtering, the power of the magnetron sputtering is 0-300W, but not 0, and the time of the magnetron sputtering is 0-300s, but not 0.
[0043] In the present invention, the catalyst layer and the metal layer only uniformly cover the surface of the micro-nano pores, but are not filled therein. Through the hot pressing in step S2, the ion exchange membrane can be pressed into the micro-nano pores to fill the pores.
[0044] In some embodiments, in step S2, the ion exchange membrane comprises a proton exchange membrane or an anion exchange membrane; preferably, the proton exchange membrane comprises a perfluorosulfonic acid membrane.
[0045] In the present invention, in step S2, one side of the ion exchange membrane is bonded to the metal layer, and the other side is used to support the cathode catalyst layer; preferably, the edge of the template is aligned with the edge of the cathode catalyst layer.
[0046] In some embodiments, in step S2, the temperature of the hot pressing is 100-150°C.
[0047] In some embodiments, in step S2, the pressure of the hot pressing is 1-10 MPa.
[0048] In some embodiments, in step S2, the hot pressing time is 3 minutes to 20 hours.
[0049] In some embodiments, in step S3, the alkaline washing reagent includes sodium hydroxide, and preferably, the concentration of the sodium hydroxide is 0.1-10M.
[0050] In some embodiments, in step S3, the alkali washing time is 5-60 hours.
[0051] In some embodiments, in step S3, the temperature of the alkali washing is 10-60°C.
[0052] In some embodiments, in step S3, after the material B is subjected to the alkali washing, a protonation step is also performed.
[0053] In a preferred embodiment, the protonation reagent includes sulfuric acid. Preferably, the concentration of the sulfuric acid is 0.1-2M.
[0054] In a preferred embodiment, the protonation time is 12-60 h.
[0055] In a preferred embodiment, the protonation temperature is 10-60°C.
[0056] Among them, those skilled in the art should know that the material C needs to be dried after the protonation.
[0057] In the present invention, metal nanowires are grown in-situ on the metal layer without catalyst particles through the reaction in step S4.
[0058] In some embodiments, in step S4, the concentration of the reducing agent is 0-10 M, but not 0.
[0059] In some embodiments, in step S4, the reducing agent includes one or more of formic acid, sodium borohydride and triethylene glycol. Preferably, the reducing agent is formic acid.
[0060] In some embodiments, in step S4, the concentration of the metal salt solution is 0-10 mM, but not 0.
[0061] In some embodiments, in step S4, the metal salt solution includes one or more of chloroplatinic acid, chloroauric acid, chloropalladic acid, and chloroiridic acid.
[0062] In some embodiments, in step S4, the mixed solution further includes a surfactant; preferably, the concentration of the surfactant is 0-5M, but not 0; preferably, the surfactant includes hexadecyltrimethylammonium bromide and / or hexadecyltrimethylammonium chloride.
[0063] In some embodiments, in step S4, the reaction temperature is 0-300°C.
[0064] In some embodiments, in step S4, the reaction time is 0-48 hours.
[0065] The present invention also provides a catalyst coating membrane, which is prepared by the above-mentioned method for preparing the catalyst coating membrane.
[0066] The present invention also provides a membrane electrode, which comprises the catalyst-coated membrane as described above.
[0067] In some embodiments, the membrane electrode comprises a first gas-liquid diffusion layer, the catalyst coated membrane, a cathode catalyst layer and a second gas-liquid diffusion layer in sequence, wherein the multi-stage catalyst layer side of the catalyst coated membrane is adjacent to the first gas-liquid diffusion layer, and the ion exchange membrane side of the catalyst coated membrane is adjacent to the cathode catalyst layer.
[0068] The present invention also provides a use of the membrane electrode as described above in a water electrolysis device.
[0069] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0070] The reagents and raw materials used in the present invention are commercially available.
[0071] The positive and progressive effects of the present invention are:
[0072] The product of the present invention makes the multi-stage catalytic layer side of the catalyst-coated membrane super hydrophilic through the design of multi-stage nano-catalytic layers and metal nanowires, effectively solving the problem of large mass transfer resistance of the traditional catalytic layer; at the same time, the structure improves the contact at the diffusion layer / catalytic layer interface, improves the utilization rate of the catalyst, thereby reducing the operating cost of the membrane electrode in the hydrogen production process, laying a foundation for its efficient operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] Figure 1 Shown is the SEM image of the anodized aluminum (AAO) template of Example 1.
[0074] Figure 2 Shown are the SEM and EDS images of the product obtained in step S3 of Example 1.
[0075] Figure 3 Shown is a schematic diagram of the structure of the catalyst-coated proton membrane of Example 1.
[0076] Figure 4 Shown is a SEM image of the catalyst-coated proton membrane of Example 2.
[0077] Figure 5 Shown is a partially enlarged SEM image of the catalyst-coated proton membrane of Example 2.
[0078] Figure 6 Shown is a comparison of polarization curves of Example 1 and a conventional MEA having the same catalyst loading.
[0079] Figure 7 Shown is the contact angle of the proton membrane coated on the catalytic layer surface of the catalyst of Example 2 with water.
[0080] Figure 8 Shown is the contact angle between the proton membrane coated on the catalytic layer surface of the catalyst of Comparative Example 1 and water.
[0081] Description of reference numerals:
[0082] Metal Nanowires1
[0083] Catalytic layer 2
[0084] Metal layer 3
[0085] Proton exchange membrane4. DETAILED DESCRIPTION
[0086] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0087] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or under conditions recommended by the manufacturers.
[0088] In addition to the specific methods, equipment, and materials used in the embodiments, based on the understanding of the prior art by those skilled in the art and the description of the present invention, any methods, equipment, and materials of the prior art that are similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention may also be used to implement the present invention.
[0089] See also Figures 1 to 8It should be noted that the illustrations provided in this embodiment are only used to illustrate the basic concept of the present invention in a schematic manner, and the illustrations only show components related to the present invention rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.
[0090] In Examples 1-2 and Comparative Example 1, the sources of the raw materials used are as follows: perfluorosulfonic acid membranes Nafion 115 and 117 are from Chemours company; H2SO4, NaOH, and (CH3)2CHOH are all from Sinopharm Chemical Reagent Co., Ltd.
[0091] Example 1
[0092] The method for preparing the catalyst coated membrane of this embodiment comprises the following steps:
[0093] S1. Introducing a catalyst slurry and a metal into a soluble template in sequence to form a material A, wherein the material A comprises a soluble template, a catalyst layer and a metal layer arranged in sequence;
[0094] Wherein, the soluble template is anodized aluminum oxide (AAO) template. Figure 1 The SEM image of the anodic aluminum oxide (AAO) template of this embodiment is shown. The template has a plurality of orderly arranged conical pore structures, the maximum cross-sectional diameter of the cone is 800nm, the distance between two adjacent cones is 500nm, and the depth of the cone is 700nm;
[0095] Before step S1, the soluble template is first ultrasonically cleaned in an ethanol solution for 2 minutes, then ultrasonically cleaned in deionized water for 2 minutes, and dried for later use;
[0096] The preparation method of the catalyst layer is as follows: 8 mg IrO2, 64 mg perfluorosulfonic acid resin, 150 mg water and 100 mg isopropanol solution are mixed and ultrasonically dispersed for 0.5 h to obtain a catalyst slurry. 50 mg of the catalyst slurry is sprayed on the surface of the AAO template.
[0097] The preparation method of the metal layer is: placing the catalyst layer containing the template in the cavity of an ion sputtering apparatus, sputtering with Pt, a sputtering current of 25 mA, and a sputtering time of 20 seconds; and obtaining a catalyst layer with an ultra-thin metal layer on one side and a template on the other side.
[0098] S2, hot pressing material A on one side of the metal layer with a proton exchange membrane to obtain material B, the hot pressing temperature is 180°C, the pressure is 10MPa, and the time is 12h; perfluorosulfonic acid membrane Nafion 115 is used as the proton exchange membrane;
[0099] S3, soaking material B in a 2M NaOH solution at 25°C for 10 hours, removing the template, and then soaking it in 0.5M sulfuric acid for protonation. The protonation time is 60 hours at a temperature of 25°C, and then drying to obtain material C;
[0100] Figure 2 The SEM and EDS images of the product obtained in step S3 of this embodiment are shown. Figure 2 Part a is a SEM image of the ordered structure of the metal Pt layer in this embodiment; Figure 2 The bf parts are the EDS element mapping images of the product, where the b part is the arrangement and distribution of the C element; the c part is the arrangement and distribution of the F element; the d part is the arrangement and distribution of the Ir element; the e part is the arrangement and distribution of the Pt element; and the f part is the EDS element mapping image of the combined elements in the product. Figure 2 It can be seen that the catalytic layer has an ordered array structure and a uniform distribution of the catalytic layer and the metal layer.
[0101] S4. The preparation method of the mixed solution is as follows: 20 ml of water, 200 μL of formic acid and 3 mL of 0.02 mol / L chloroplatinic acid aqueous solution are added into a 100 mL beaker, and the mixture is fully mixed to obtain the mixed solution.
[0102] Material C was immersed in the mixed solution and reacted at 50° C. for 12 h. After being taken out, it was cleaned in ultrapure water.
[0103] Figure 3 It can be a schematic diagram of the structure of the catalyst coating membrane of this embodiment. Figure 3 As shown, the catalyst coating membrane includes a proton exchange membrane 4 and a multi-stage catalytic layer arranged on one side of the proton exchange membrane 4; the multi-stage catalytic layer includes a plurality of orderly arranged micro-nano units, and the micro-nano units are sequentially provided with a metal layer 3, a catalytic layer 2 and a metal nanowire 1 in a direction away from the proton exchange membrane 4. The loading of the metal Pt layer is 4.2 μg / cm 2 The micro-nano unit is conical; the thickness of the micro-nano unit is 700nm; the diameter of the maximum cross section of the micro-nano unit is 800nm; the distance between two adjacent micro-nano units is 500nm; the loading of the metal Pt nanowire is 80.7μg / cm 2 , in the shape of a sea urchin; the proton exchange membrane 4 is a perfluorosulfonic acid membrane.
[0104] Example 2
[0105] The method for preparing the catalyst coated membrane of this embodiment comprises the following steps:
[0106] S1. Introducing a catalyst slurry and a metal into a soluble template in sequence to form a material A, wherein the material A comprises a soluble template, a catalyst layer and a metal layer arranged in sequence;
[0107] The soluble template is an anodic aluminum oxide (AAO) template, which has a plurality of orderly arranged conical pore structures, the maximum cross-sectional diameter of the cone is 600nm, the distance between two adjacent cones is 200nm, and the depth of the cone is 2000nm;
[0108] Before step S1, the soluble template is first ultrasonically cleaned in an ethanol solution for 2 minutes, then ultrasonically cleaned in deionized water for 2 minutes, and dried for later use;
[0109] The preparation method of the catalyst layer is as follows: 8 mg Ir, 50 mg perfluorosulfonic acid resin, 200 mg water and 300 mg tert-butyl alcohol solution are mixed and ultrasonically dispersed for 1 hour to obtain a catalyst slurry. 20 mg of the catalyst slurry is sprayed on the surface of the AAO template.
[0110] The preparation method of the metal layer is: placing the catalyst layer containing the template in the cavity of a magnetron sputtering coater, sputtering with iridium, the sputtering power is 120W, and the sputtering time is 50s; obtaining a catalyst layer with an ultra-thin metal layer on one side and a template on the other side.
[0111] S2, hot pressing material A on one side of the metal layer with a proton exchange membrane to obtain material B, the hot pressing temperature is 120°C, the pressure is 10 MPa, and the time is 20 min; perfluorosulfonic acid membrane Nafion 117 is used as the proton exchange membrane;
[0112] S3, soaking material B in 1M NaOH solution for 20 hours, removing the template, and then soaking it in 1M sulfuric acid for protonation. The protonation time is 48 hours at a temperature of 40°C, and then drying to obtain material C;
[0113] S4. The preparation method of the mixed solution is as follows: 100 ml of water, 3 ml of triethylene glycol, 12 mg of hexadecyltrimethylammonium bromide and 2 ml of 0.05 mol / L chloroiridic acid aqueous solution are added into a 500 ml beaker, and the mixture is fully mixed to obtain the mixed solution.
[0114] Material C was immersed in the mixed solution and reacted at 200° C. for 1 h. After being taken out, it was cleaned in ultrapure water.
[0115] The catalyst coating membrane includes a proton exchange membrane and a multi-stage catalytic layer arranged on one side of the proton exchange membrane; the multi-stage catalytic layer includes a number of orderly arranged micro-nano units, and the micro-nano units are sequentially provided with a metal layer, a catalytic layer and metal nanowires in the direction away from the proton exchange membrane. The loading of the metal Ir layer is 6.4μg / cm 2The micro-nano unit is conical; the thickness of the micro-nano unit is 2000nm; the diameter of the maximum cross section of the micro-nano unit is 600nm; the distance between two adjacent micro-nano units is 200nm; the loading of the metal Ir nanowire is 56.3μg / cm 2 . Figure 4 is a SEM image of the catalyst coating membrane of this embodiment; Figure 5 This is a partially enlarged SEM image of the catalyst coating membrane of this embodiment. It can be seen from the image that the catalyst layer of this embodiment presents a sea urchin-like structure, and the nanowires are stacked on each other and the structure is relatively compact.
[0116] Comparative Example 1
[0117] The method for preparing the catalyst coated membrane of this embodiment comprises the following steps:
[0118] S1. Introducing a catalyst slurry and a metal into a soluble template in sequence to form a material A, wherein the material A comprises a soluble template, a catalyst layer and a metal layer arranged in sequence;
[0119] The soluble template is an anodic aluminum oxide (AAO) template, which has a plurality of orderly arranged cylindrical channel structures, the cross-sectional diameter of the cylinder is 800nm, the distance between two adjacent cylinders is 300nm, and the depth of the cylinder is 500nm;
[0120] Before step S1, the soluble template is first ultrasonically cleaned in an ethanol solution for 2 minutes, then ultrasonically cleaned in deionized water for 2 minutes, and dried for later use;
[0121] The preparation method of the catalyst layer is as follows: 8 mg IrO2, 100 mg perfluorosulfonic acid resin, 300 mg water and 350 mg ethanol solution are mixed and ultrasonically dispersed for 1 hour to obtain a catalyst slurry. 60 mg of the catalyst slurry is sprayed on the surface of the AAO template.
[0122] The preparation method of the metal layer is: placing the catalyst layer containing the template in the cavity of an ion sputtering apparatus, sputtering with Pt, a sputtering current of 40 mA, and a sputtering time of 10 seconds; and obtaining a catalyst layer with an ultra-thin metal layer on one side and a template on the other side.
[0123] S2. Material A is hot pressed on one side of the metal layer with a proton exchange membrane to obtain material B. The hot pressing temperature is 100°C, the pressure is 15 MPa, and the time is 10 min. Perfluorosulfonic acid membrane Nafion 115 is used as the proton exchange membrane.
[0124] S3. Material B was first immersed in a 3M NaOH solution for 8 hours to remove the template, and then immersed in 1M sulfuric acid for protonation. The protonation time was 24 hours at a temperature of 50° C. After drying, the catalyst coating membrane was obtained.
[0125] The catalyst coating membrane does not contain metal nanowires, but only contains a catalytic layer, a metal layer and a proton exchange membrane arranged in sequence.
[0126] Effect Example 1
[0127] The catalyst coated membranes of Examples 1, 2 and Comparative Example 1 were used to prepare membrane electrodes according to conventional methods in the art. Specifically, the membrane electrode sequentially comprises a first gas-liquid diffusion layer, a catalyst coated membrane, a cathode catalyst layer and a second gas-liquid diffusion layer, wherein the catalyst layer side of the catalyst coated membrane is adjacent to the first gas-liquid diffusion layer, and the other side (blank side) of the catalyst coated membrane is adjacent to the cathode catalyst layer; wherein the cathode catalyst layer is obtained by coating a Pt / C cathode catalyst on the blank side of the catalyst coated membrane, and the first gas-liquid diffusion layer and the second gas-liquid diffusion layer are both titanium felt.
[0128] 1. Polarization curve test
[0129] The polarization curves of the membrane electrode of Example 1 and the conventional membrane electrode with the same catalyst loading were tested using a high-performance battery testing system of model BTS-4000 (Shenzhen Xinwei Electronics Co., Ltd.). Figure 6 The polarization curves of Example 1 and conventional MEA with the same catalyst loading are shown, where the catalyst loading is 0.15 mg / cm 2 , the test temperature is 60° C. As can be seen from the figure, the cell pressure of the membrane electrode with both ultra-thin metal layer and multi-level micro-nano structure (Example 1) is lower than the cell pressure of the traditional membrane electrode. Therefore, the water electrolysis performance of the membrane electrode of Example 1 is better than that of the traditional MEA.
[0130] 2. Water contact angle test
[0131] The contact angle between the catalyst layer surface of the catalyst coated membrane of Example 2 and Comparative Example 1 and water was tested using a contact angle measuring instrument of model SL200KS (from Shanghai Solon Information Technology Co., Ltd.). Figure 7 Shown is the contact angle of the catalyst layer surface of the catalyst coated membrane of Example 2 with water. Figure 8 Shown is the contact angle of the catalyst layer surface of the catalyst coated membrane of Comparative Example 1 with water.
[0132] from Figure 7 It can be seen that the contact angle of the catalytic layer (Example 2) with water, which has both an ultra-thin metal layer and a multi-level micro-nano structure, is as low as 8.74°, showing super hydrophilicity; Figure 8 It can be seen that the contact angle of the catalytic layer with only an ultra-thin metal layer and no metal nanowires (Comparative Example 1) with water is 46.77°, which is greater than that of Example 2, and its hydrophilicity is significantly lower than that of Example 2.
[0133] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A catalyst coated membrane, It is characterized in that It includes an ion exchange membrane and a multi-stage catalyst layer arranged on one side of the ion exchange membrane; The multi-stage catalytic layer comprises a plurality of orderly arranged micro-nano units, wherein the micro-nano units are provided with a metal layer, a catalytic layer and metal nanowires in sequence in a direction away from the ion exchange membrane.
2. The catalyst coated membrane according to claim 1, It is characterized in that The micro-nano unit is cylindrical or conical; And / or, the thickness of the micro-nano unit is 200nm-3μm; And / or, the diameter of the maximum cross section of the micro-nano unit is 10nm-1μm; And / or, the distance between two adjacent micro-nano units is 100nm-1μm; And / or, the material of the catalytic layer includes IrO 2 ; And / or, the catalyst layer has a porous structure, and the metal nanowires are in contact with the metal layer through gaps on the catalyst layer.
3. The catalyst coated membrane according to claim 1, It is characterized in that The material of the metal layer includes one or more of Au, Pt, Ir and Pd; And / or, the material of the metal nanowires includes one or more of Au, Pt, Ir and Pd; and / or, the material of the metal layer is the same as the material of the metal nanowires; And / or, the loading of the metal layer is 0-100 μg / cm 2 , but not 0; And / or, the loading of the metal nanowires is 0-0.5 mg / cm 2 , but not 0; and / or, the metal nanowires are in one or more of a sea urchin shape, a spherical shape, and a coral shape; And / or, the ion exchange membrane includes a proton exchange membrane or an anion exchange membrane.
4. A method for preparing a catalyst coated membrane, It is characterized in that It includes the following steps: S1. Introducing a catalyst slurry and a metal into a template having a micro-nano structure in sequence to form a material A, wherein the material A comprises a metal layer, a catalyst layer and a template arranged in sequence; S2, attaching the ion exchange membrane to the metal layer, and then hot pressing to obtain material B, wherein the temperature of the hot pressing is 60-200° C., and the pressure of the hot pressing is 1-60 MPa; S3, alkali washing the material B to obtain material C; the alkali washing is used to remove the template; S4, immersing the material C in the mixed solution to react and form metal nanowires; The mixed solution includes a reducing agent and a metal salt solution.
5. The method for preparing a catalyst coated membrane according to claim 4, It is characterized in that In step S1, the material of the template includes anodized aluminum; and / or, the catalyst slurry comprises a catalyst, a stereopolymer resin and a solvent; Preferably, the catalyst comprises IrO 2 ; Preferably, the stereopolymer resin comprises perfluorosulfonic acid resin; Preferably, the solvent comprises water and alcohol; more preferably, the mass ratio of the catalyst, stereopolymer resin, water and alcohol is 1:(1-20):(1-50):(1-50); Preferably, the method for preparing the catalyst slurry comprises ultrasonically mixing the catalyst, stereopolymer resin and solvent; more preferably, the ultrasonic mixing time is 0.1-4h; And / or, the catalyst slurry is introduced by spraying; and / or, the metal comprises one or more of Au, Pt, Ir and Pd; And / or, the method of introducing the metal includes ion sputtering and / or magnetron sputtering; preferably, when the method of introducing the metal is ion sputtering, the current of the ion sputtering is 0-50mA, but not 0, and the time of the ion sputtering is 0-360s, but not 0; preferably, when the method of introducing the metal is magnetron sputtering, the power of the magnetron sputtering is 0-300W, but not 0, and the time of the magnetron sputtering is 0-300s, but not 0.
6. The method for preparing a catalyst coated membrane according to claim 4, It is characterized in that In step S2, the ion exchange membrane includes a proton exchange membrane or an anion exchange membrane; preferably, the proton exchange membrane includes a perfluorosulfonic acid membrane; And / or, in step S2, one side of the ion exchange membrane is bonded to the metal layer, and the other side is used to support the cathode catalyst layer; preferably, the edge of the template is aligned with the edge of the cathode catalyst layer; And / or, in step S2, the temperature of the hot pressing is 100-150°C; And / or, in step S2, the hot pressing pressure is 1-10 MPa; And / or, in step S2, the hot pressing time is 3min-20h; And / or, in step S3, the alkali washing reagent includes sodium hydroxide, preferably, the concentration of the sodium hydroxide is 0.1-10M; And / or, in step S3, the alkali washing time is 5-60h; And / or, in step S3, the temperature of the alkali washing is 10-60°C; And / or, in step S3, after the material B is subjected to the alkali washing, a protonation step is also performed; Preferably, the protonated reagent includes sulfuric acid, and preferably, the concentration of the sulfuric acid is 0.1-2M; Preferably, the protonation time is 12-60h; Preferably, the protonation temperature is 10-60°C.
7. The method for preparing a catalyst coated membrane according to claim 4, It is characterized in that In step S4, the concentration of the reducing agent is 0-10M, but not 0; and / or, the reducing agent comprises one or more of formic acid, sodium borohydride and triethylene glycol, preferably, the reducing agent is formic acid; and / or, the concentration of the metal salt solution is 0-10 mM, but not 0; And / or, the metal salt solution includes one or more of chloroplatinic acid, chloroauric acid, chloropalladic acid and chloroiridic acid; And / or, the mixed solution further comprises a surfactant; preferably, the concentration of the surfactant is 0-5M, but not 0; preferably, the surfactant comprises hexadecyltrimethylammonium bromide and / or hexadecyltrimethylammonium chloride; And / or, the reaction temperature is 0-300°C; And / or, the reaction time is 0-48h.
8. A catalyst coated membrane, It is characterized in that The catalyst coating membrane is prepared by the method for preparing the catalyst coating membrane as described in any one of claims 4 to 7.
9. A membrane electrode, It is characterized in that It comprises a catalyst coated membrane as described in any one of claims 1 to 3 and 8; Preferably, the membrane electrode comprises a first gas-liquid diffusion layer, the catalyst coated membrane, a cathode catalyst layer and a second gas-liquid diffusion layer in sequence, wherein the multi-stage catalyst layer side of the catalyst coated membrane is adjacent to the first gas-liquid diffusion layer, and the ion exchange membrane side of the catalyst coated membrane is adjacent to the cathode catalyst layer.
10. Use of the membrane electrode as claimed in claim 9 in a water electrolysis device.
